Probabilistic treatment of IEC 61400‐1 standard based extreme wind events - Wim Bierbooms; Dick Veldkamp (Wind Energy)
Abstract The procedure to estimate the amplitude of the special wind events according to IEC 61400‐1 as proposed by Larsen is reviewed. Corrections are specified that yield larger amplitudes for the extreme operating gust (EOG) and the extreme coherent gust with simultaneous direction change (ECD). For the ECD case, distributions for longitudinal and lateral gust amplitudes are derived and applied in simulations to derive the load distribution, from which the 50‐year extreme load can be found. Results are compared with the calculation with the conventional ECD: In the example calculation, the 50‐year values of both blade root bending moment and tip deflection are smaller than the conventional values.